Limiting Behavior of the Kinetic Theory for Systems with Multistep Interaction - Humenyuk, Y.A.; Tokarchuk, M.V. (Відділення фізики і астрономії НАН України, 2010)
The kinetic theory of mixtures with a multistep potential (MSP) is considered. A passage to the limit of the smooth continuous potential for the kinetic equation and the potential energy density balance equation is analyzed. When the “hard spheres + soft tail” form for the limiting potential is chosen, the kinetic equation reduces to that of the kinetic variational theory (KVT), while the limiting balance equation for the kinetic energy density differs from its KVT counterpart. Розглянуто кiнетичну теорiю сумiшей з багатосходинковим потенцiалом взаємодiї. Проаналiзовано граничний перехiд до плавного неперервного потенцiалу для кiнетичного рiвняння i рiвняння балансу для густини потенцiальної енергiї. Коли граничний потенцiал вибрано у формi “твердi кульки + плавний хвiст”, кiнетичне рiвняння зводиться до рiвняння кiнетичної варiацiйної теорiї (КВТ), однак граничне рiвняння балансу для густини кiнетичної енергiї вiдрiзняється вiд вiдповiдного рiвняння КВТ.